Implications of Data Protection Law on Media and Communication in Nigeria - Muhammad Danjuma Abubakar; Hauwa Kawo Mohammed; Ekpali Joseph Saint; Muhammad Ridwan (Polit Journal Scientific Journal of Politics, 2025)
The enactment of data protection laws has significantly reshaped the landscape of media and communication in Nigeria. As the country increasingly integrates digital technology into journalism, broadcasting, and online communication, the legal framework surrounding data privacy has become a crucial factor in defining how information is collected, stored, and disseminated. The Nigeria Data Protection Act (NDPA) and other regulatory instruments seek to balance the rights of individuals to privacy with the freedom of expression and access to information, both of which are essential for a thriving democratic society. This paper attempts to explore the possible effect of the new data protection law in Nigeria, on media and communications, specifically PR, advertising and journalism practices respectively. The paper employs qualitative methodology and relies on the interviews; using snowballing and purposive techniques. The study utilizes interpretative phenomenological analysis using in-depth interview. The outcome of the study shows that Mass Communications and its varied specializations (Advertising, PR and Journalism) rely heavily on reliable data since it deals with audiences of distinct characteristics and so messages tailored to these audiences’ needs are backed by the knowledge of their personal data. The study concludes that as a fundamental human right that data protection is, relevant laws that guarantee it are welcome but amendments of such laws have to be continuous and addition to its global harmonization to fill up numerous gaps to ensure fullest protection.